GAMBARAN PENGETAHUAN MASYARAKAT TERKAIT COVID-19 - Aulia Sadeva; Arneliwati Arneliwati; Nopriadi Nopriadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Coronavirus Disease 2019 (COVID-19) is a new disease that causes pneumonia and respiratory problems. The increase in COVID-19 cases continues to occur in Indonesia, making the government make various efforts to prevent the spread of COVID-19 more widely, one of which is by increasing public knowledge about COVID-19. Good public knowledge about COVID-19 will be useful in preventing the spread of COVID-19. This study aims to determine the description of public knowledge about COVID-19. The design of this research is descriptive quantitative research using univariate analysis. Data were collected using a questionnaire to 93 respondents with purposive sampling technique in the community in RW 011, North Tangkerang Village, Pekanbaru City. Data analysis used univariate analysis. The measuring instrument used is a questionnaire via google form consisting of 9 questions that have been tested for validity for 9 statements obtained r count 0.477 - 0.745 > r table (0.4444). Reliability test obtained Cronbach alpha > r table (0.776 > 0.4444). The results showed that the community had good knowledge about COVID-19, as many as 88 respondents (94.6%).Keywords: COVID-19, Knowledge, Health Protocol